Organizations Unfettered: Organizational Form in an Information-Intensive Economy - Child, John; McGrath, Rita Gunther (Academy of Management Journal, 2001)
The transition from an economy based on materials to an economy based on flows of information has created considerable challenges for organization design by unfettering many organizational aspects from physical constraints. We view the resulting new organizational forms as coping with four core issues: interdependence, disembodiment, velocity, and power. The nine articles in this special research forum provide evidence on how forms have changed, as well as on which aspects of traditional theorizing are likely to continue to be robust. Core themes reflected are an acceptance of contradiction and paradox, a shift in the goal of organizing from buffering against uncertainty to responding to it, a strategic focus on structure and process design, a reemphasis on the social and interpersonal, and a reemergence of issues of legitimacy.